Iodine deficiency in children: A comparative study in two districts of south-interior Karnataka, India - Mansoor Ahmed; Syed Y Zama; Vadiraja Nagarajarao; Mudassir A Khan (Journal of Family and Community Medicine, 2014)
Introduction: Iodine is an essential component of the hormones produced by the thyroid gland that are essential for mammalian life. Although goiter is the most visible sequelae of iodine deficiency, the major impact of hypothyroidism as a result of iodine deficiency is impaired neurodevelopment, particularly early in life. According to the World Health Organization, it is the single most preventable cause of mental retardation and brain damage. The simplest, most effective and inexpensive preventive method is the consumption of iodized salt. Objectives: The objective of the following study is to estimate the prevalence of goiter in children in the rural areas of Mysore and Coorg districts in India and estimate iodine levels in salt samples. Materials and Methods: A cross-sectional study in the age group of 6-12 years, using population proportionate to size systematic sampling method. The total sample size was 10,082: out of which 5337 was from Mysore and the rest from Coorg district. Clinical examination of the thyroid gland was done and salt samples collected for the estimation of Iodine. Results: The total prevalence of goiter was 19.01% in children of 6-12 years in Coorg district and 8.77% in Mysore district and it was more in females than in males. Conclusions: It was observed that iodine deficiency disorders is endemic in both districts, with a prevalence of 19.01% in children aged 6-12 years in Coorg district and 8.77% in Mysore district. Analysis of salt samples suggested that most of the samples were inadequately iodised (73.92% in Coorg and 45.92% in Mysore).